Contextual Effects of Immigrant Presence on Populist Radical Right Support: Testing the "Halo Effect" on Front National Voting in France. (April 2021) - Evans, Jocelyn; Ivaldi, Gilles
This paper examines the relationship between immigration and populist radical right (PRR) support, based on an analysis of the contextual effects of immigrant presence on Front National vote in France in 2017. Using a unique set of survey data geolocalising respondents at the subcommunal level, it finds evidence for the existence of a curvilinear "halo effect, " with substantial increases in the probability of PRR vote in areas surrounding communities with significantly higher-than-average immigrant populations, and independent of other socio-economic context, as well as individual socio-demographic characteristics. Most importantly, a path analysis confirms the presence of individual attitudinal mediators of this halo effect on PRR vote, thus testing the foundation of the halo, namely that the contextual effects of immigrant presence act on attitudes which drive PRR support. These findings provide a significant step forward in understanding the mechanisms linking subjective experience of immigration with voting for the populist radical right.